2021
DOI: 10.1055/s-0041-1731739
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Survival of a Varus–Valgus Constrained Implant following One-Stage Revision for Periprosthetic Joint Infection: A Single-Center Study

Abstract: Revision total knee arthroplasty (TKA) is challenging to perform in patients with periprosthetic joint infection (PJI) due to the difficulty of eradicating the infection and potential for bone and ligamentous deficits. The current study aimed to evaluate the midterm survival of varus–valgus constrained (VVC) implants used in one-stage revision TKA for chronic PJI at our institution. This retrospective analysis included 132 patients with chronic PJI who underwent one-stage revision using a VVC implant. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Nevertheless, this study showed an increased overall revision rate after rotating hinge prostheses with an overall survival rate of 75% at 6 years [27]. In contrast, a retrospective study of 132 patients with single-stage rotation and CCK prostheses showed an eradication rate of 91% and an overall survival rate of 82.7% at 5 years [28]. Overall, however, it should be noted that the data available for the comparison of different implant systems in PJI treatment are still very limited.…”
Section: Discussioncontrasting
confidence: 59%
“…Nevertheless, this study showed an increased overall revision rate after rotating hinge prostheses with an overall survival rate of 75% at 6 years [27]. In contrast, a retrospective study of 132 patients with single-stage rotation and CCK prostheses showed an eradication rate of 91% and an overall survival rate of 82.7% at 5 years [28]. Overall, however, it should be noted that the data available for the comparison of different implant systems in PJI treatment are still very limited.…”
Section: Discussioncontrasting
confidence: 59%
“…After excluding duplicates, 343 studies were included, and after evaluation of the title and abstract, 21 studies were analyzed. After assessing the eligibility of the full-text articles according to the inclusion and exclusion criteria and screening the bibliography of each article to find additional relevant publications, 18 clinical studies were selected and included in this systematic review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The PRISMA flowchart with the research strategy is shown in Fig.…”
Section: Search Strategy and Study Screeningmentioning
confidence: 99%
“…Eighteen clinical studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were included in the final analysis (Fig. 1) [17].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations